2021
DOI: 10.29240/ef.v5i1.2173
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of English Sentence Structure in Students’ Written Paragraphs

Abstract: This research aimed to find out the types of sentence structure errors in English paragraphs written by tertiary English students and the factors causing the errors. This research employed an explanatory mixed-method design. Fourth-semester students from the English department of IAIN Curup were engaged as the subjects of this research. Positivism-governed document analyses and constructivism-based interviews were conducted to solicit the data as desired. The quantitative findings garnered from document analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Octaberlina and Muslimin (2022) admitted that addition was the most dominant error in students' thesis proposal writing. Sundari et al, (2021) also found that students made errors in omission, addition, misformation, and misordering of writing recount paragraphs with omission as the most dominant error. Furthermore, Imaniar (2018) showed that omission was the type of error made mostly by Indonesian junior high students in writing descriptive paragraphs.…”
Section: Introductionmentioning
confidence: 87%
“…Octaberlina and Muslimin (2022) admitted that addition was the most dominant error in students' thesis proposal writing. Sundari et al, (2021) also found that students made errors in omission, addition, misformation, and misordering of writing recount paragraphs with omission as the most dominant error. Furthermore, Imaniar (2018) showed that omission was the type of error made mostly by Indonesian junior high students in writing descriptive paragraphs.…”
Section: Introductionmentioning
confidence: 87%
“…However, many EFL learners experienced difficulty in writing sentences well in the target language. Many EFL learners experienced difficulty in sentence writing in the aspects of omission, addition, malformation, and disordering [29]. In addition, the teaching of sentence writing for EFL learners concerned with many issues such as writing instruction was concerned with the correctness of form over function so that students spent time in copying models of sentences rather than expressing their own ideas creatively; as a result, what students produced tended to be limited to writing practice in realia [1].…”
Section: Introductionmentioning
confidence: 99%
“…There are some previous researches discussing about error analysis on sentence construction. The first one is written by Sundari, et. al.…”
Section: Introductionmentioning
confidence: 99%